Inguinal Hernia in Preterm Infants: Optimal Timing of Herniorrhaphy to Prevent Preoperative Incarceration and Postoperative Apnea - Jaeho Shin; Ga Won Jeon (Korean Society of Neonatology, 2020)
Purpose The objective of this study was to determine the optimal timing of inguinal herniorrhaphy in preterm infants to reduce the risks of preoperative incarceration and postoperative complications. Methods Preterm infants with gestational age (GA) of <37 weeks who had inguinal herniorrhaphy before the age of 6 months were enrolled. Early repair was defined as undergoing herniorrhaphy before discharge from the neonatal intensive care unit (NICU), and late repair was defined as undergoing herniorrhaphy as an outpatient after discharge from the NICU. Results The incidence rates of preoperative incarceration and recurrence were not significantly different between the two groups. Postoperative apnea and mechanical ventilation were more frequent in the early-repair group than in the late-repair group. Postoperative apnea was more frequent in the early-repair group after adjustments for GA and birth weight. However, no significant difference in postoperative mechanical ventilation was found between the two groups after adjustments for GA and birth weight. The incidence of postoperative apnea was associated with small weight at repair, early repair, general anesthesia, younger GA, small weight at birth, and bronchopulmonary dysplasia. Contralateral metachronous hernia was most frequent in infants with small weight at repair, early repair, very low birth weight (VLBW), male sex, and right-sided hernia. Conclusion Late repair was safe and did not increase the risk of incarceration or recurrence, but decreased the risks of postoperative apnea and metachronous hernia. Regional anesthesia could reduce the risk of postoperative apnea. Male infants born with VLBWs and right-sided hernia should be followed up carefully for metachronous hernia.